Bispecific antibody treatment of multiple myeloma: latest updates from the 2022 ASH annual meeting - Xuejiao Yin; Yi Liu; Jianai Sun; Hongyan Tong; Haitao Meng; Liangshun You (SAGE Publishing, 2023)
Background: Effective novel therapies for multiple myeloma (MM) patients who are unresponsive to conventional treatments (triple-class refractory) are an urgent need. Bispecific antibodies (BsAbs) offer a promising new approach to stimulate T cells and induce tumor cell death by targeting molecules on the surface of malignant plasma cells and CD3 on the surface of T cells. Objectives: Addressing the issue of improving the prognosis of triple-class refractory MM patients has become a significant clinical challenge. Design: This is a brief report. Methods: This article summarizes the latest updates of BsAbs treatment of MM from the 2022 ASH annual meeting. Results: BsAbs that target B-cell maturation antigen and G protein-coupled receptor family C group 5 memberD have demonstrated remarkable clinical activity and favorable safety profiles. Many potential targets for myeloma cells are currently undergoing phase I/II clinical trials, and these off-the-shelf bispecific molecules are likely to become a critical part of the MM treatment landscape. Conclusion: This article provides an overview of the latest advances in BsAbs immunotherapy for refractory and relapsed MM and highlights significant findings from the 2022 ASH annual meeting.